Towards a Phenomenology of Being-at-Home and Being-Exposed: International Graduate Centre for the Study of Culture (Giessen) (KULT_online, 2018)
John Russon’s new book Sites of Exposure investigates the distinct character of basic human experience and ponders its constitutive role in the formation of meaning. Russon argues that our experiential life and our sense of self is essentially defined by a conflictual intertwining of “home” and “exposure.” Taking a phenomenological perspective, the author considers the philosophical relevance of theorizing both personal and interpersonal reality as it is embodied and lived. In doing so, Russon not only elucidates the transformative power of artistic expression, but also unfolds the ways phenomenology serves as a valuable resource and reference point for doing contemporary social and political criticism.